PENINGKATAN KINERJA OPERASIONAL DENGAN MENGAKTIFKAN STANDAR OPERASIONAL PROSEDUR DI JAVA ORIGIN - Liliana Dewi; Arvin Fuldyanto (Jurnal Bisnis Terapan, 2019)
Java Origin is a company that runs in fashion field. The competition of the business world become tighten in accordance with the era. Various strategies are done by the company so that the company will not be left behind by the other competitors. One of the company’s strategy is to fix internal SOP. To know the role of SOP quality control towards operational performance of Java Origin. Determination of data source use purposive sampling with two speakers from internal employeer of Java Origin. One lecturer of Java Origin and one owner of business. The method that is used in this research is descriptive qualitative method. Data analysis use data reduction. Validation and data reliability that are used membercheck and triangulation source. The result of this research is the company is still lack concept out SOP. Java Origin company need to follow the existing SOP, does not interfere work division, implement evaluation system, built up more communication.